Unscripted : a Novel - Bunn, T. Davis 1952- (Thorndike, Maine : Center Point Large Print, 2019)
Young line producer Danny Byrd is well-known in Hollywood for being someone who gets things done on time and under budget. But when his reputation takes a beating after his partner-- and former best friend-- makes off with their investors money, Danny has but one chance to redeem himself and restore his ruined career. LA lawyer Megan Pierce sacrificed years proving herself to bosses only to be disgusted by their snobbery and their specious business practices. When an opportunity to actullay make a difference comes her way, she knows she has to grab it - even though shes not entirely clear what "it" is. Danny and Megan are each others best hope for redemption. What they never could have imagined was that they might also be each others best hope for love.
Keywords: Motion picture producers and directors -- United States; Fiction; Betrayal -- Fiction; Women lawyers -- United States; Fiction; Motion pictures -- Production and direction; Fiction; Motion picture industry -- California; Los Angeles; Fiction; False imprisonment -- Fiction; Man-woman relationships -- Fiction; Los Angeles (Calif.) -- Fiction; Legal fiction (Literature); Domestic fiction; Romance fiction; Christian fiction